Static Type Checking of Model Transformation Programs - Ujhelyi, Zoltán; Horváth, Ákos; Varró, Dániel (Electronic Communications of the EASST, 2011)
Model transformation is seen as a promising approach to automate software development and verification, thus improving quality and reducing production costs significantly. However, errors of transformation programs can propagate into the generated artifacts complicating the detection of errors. The current paper proposes a static type checking approach for early detection of typing errors of partially typed transformation programs. The approach describes type safety as constraint satisfaction problems, and uses a dedicated back-annotation mechanism for error feedback.